Association of a novel nutritional index with stroke in Chinese population with hypertension: Insight from the China H-type hypertension registry study - Shi, Yumeng; Wang, Xingjiu; Yu, Chao; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Nutrition, 2023)
Objective: The abbreviated TCB index (TCBI) is a novel indicator of nutritional status, calculated by multiplying the serum values of triglycerides (TG), total serum cholesterol (TC), and body weight. The research on the relationship between this index and stroke is limited. We aimed to investigate the association between TCBI and stroke in Chinese hypertensive patients. Methods and Results: A total of 13,358 adults with hypertension from the China H-type Hypertension Registry Study were enrolled. The TCBI was calculated as TG (mg/dL) * TC (mg/dL) * body weight (kg) / 1000. The primary outcome was an incidence of stroke. Multivariable adjusted models revealed an inverse association between TCBI and the prevalence of stroke. In the fully adjusted model, the results showed that the prevalence of stroke decreased by 13% (OR, 0.87; 95% CI, 0.78–0.98, p=0.018) per SD increment of LgTCBI. When TCBI was assessed as a categorical variable, compared with those in group Q4 (TCBI≥2399), the participants in group Q3 (TCBI≥1476 and ˂2399), group Q2 (TCBI≥920 and ˂1476), and group Q1 (TCBI<920) had increases in stroke prevalence of 42% (OR, 1.42; 95% CI, 1.13–1.80; p-value = 0.003), 38% (OR, 1.38; 95% CI, 1.07–1.80; p-value = 0.014), and 68% (OR, 1.68; 95% CI, 1.24–2.27; p-value = 0.001), respectively. Subgroup analysis showed an interaction between age and TCBI and stroke (age <60 years OR, 0.69; 95% CI, 0.58–0.83; vs. age ≥60 years OR, 0.95; 95% CI, 0.84–1.07; P for interaction =0.001). Conclusion: We found an independent negative association between TCBI and the prevalence of stroke, especially in hypertensive patients aged <60 years.